Reliability and agreement of apparent chord mu measurements between static and dynamic evaluations. Issue 1 (January 2023) - Martínez-Plaza, Elena; Marcos, Mario; López-de la Rosa, Alberto; López-Miguel, Alberto; Maldonado, Miguel J.
Abstract : Galilei G4 and Topolyzer Vario provide repeatable measurements of apparent chord mu length and Cartesian coordinates; however, measurements are not interchangeable except for Y-coordinate values under photopic conditions. Abstract : Purpose: To assess the repeatability and agreement of Cartesian coordinates and the length of apparent chord mu and pupil diameter measurements during static (Galilei G4) and dynamic (Topolyzer Vario) evaluations. Setting: IOBA-Eye Institute, Valladolid, Spain. Design: Case series. Methods: 3 consecutive measurements per scenario (Galilei G4 and Topolyzer Vario under low mesopic and photopic conditions) were performed by the same clinician. The intrasession repeatability was assessed using the within-subject SD (Sw), the precision, the coefficient of variation, and the intraclass correlation coefficient (ICC). The agreement was analyzed using repeated-measures analysis of variance and the Bland-Altman method. Results: Thirty-seven healthy participants were recruited. The Sw values for chord mu parameters and pupil diameter ranged from 0.01 to 0.03 and 0.08 to 0.21, respectively. The ICC was ≥0.89 for all parameters. Galilei G4 and Topolyzer Vario under low mesopic and photopic conditions provided significantly different measures of apparent chord mu length (0.23 ± 0.11 mm, 0.30 ± 0.10 mm, and 0.25 ± 0.11 mm, respectively, P ≤ .02), X-coordinate (−0.18 ± 0.12 mm, −0.27 ± 0.11 mm, and −0.21 ± 0.12 mm, respectively, P < .001), and pupil diameter (3.38 ± 0.50 mm, 6.29 ± 0.60 mm, and 3.04 ± 0.41 mm, respectively, P < .001). Y-coordinate values obtained by Galilei G4 and Topolyzer Vario under low mesopic conditions were significantly different (0.06 ± 0.13 mm vs 0.03 ± 0.11 mm, respectively, P = .02), in contrast to Galilei G4 and Topolyzer Vario under photopic conditions (0.05 ± 0.13 mm, P = .82) and both illumination conditions of Topolyzer Vario ( P ≥ .23). Conclusions: Galilei G4 and Topolyzer Vario provide consistent measurements of apparent chord mu Cartesian coordinates and length, as well as pupil diameter; however, the measurements are not interchangeable. Ophthalmic surgeons should consider these findings when planning customized intraocular lens implantation and refractive surgery procedures.